Legal forms of cooperation between Kazakhstan and Saudi Arabia in the process of using the potential of international organizations - Al-ajmi, Mansour; Sarsembayev, Marat (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
Although Saudi Arabia and the Republic of Kazakhstan are geographically located quite far from each other, they are nevertheless linked by dozens of international legal documents that facilitate their cooperation in a number of areas. This cooperation is facilitated by the presence of Kazakhstan and Saudi Arabia in a number of universal and large regional international organizations. By combining efforts with international organizations these subjects of modern international law, member States, including Saudi Arabia and the Republic of Kazakhstan, protect their internal interests and satisfy not only their diverse needs, but also the needs of all member States of the relevant international organization. The article refers to the organizational and legal forms of cooperation between these two States within the framework of universal and regional international organizations as follows: 1) support and participation in the development of the texts of the international conventions under the auspices of the relevant international organization; 2) participation in the implementation of such international conventions in bilateral, regional and universal formats; 3) combining the efforts of two or more states in carrying out the reform of the internal mechanisms of the international organization; 4) ensuring control over all types of weapons and achieving the goals of disarmament; 5) assistance in developing a unified position of all Member States on establishing proper law and order in the international arena; 6) the creation of Islamic banking.